(untitled) (Mustansiria Dental Journal, 2025)
Background: This study aimed to investigate the relationship between psychological stress and salivary alpha -amylase levels in pediatric dental patients visit specialist versus non specialist dental clinics. Materials and Methods :Eighty male children aged 4–6 years with first dental visit were recruited from specialist and non-specialist dental clinics in Iraq. Salivary samples were collected at three time points and alpha amylase levels were analyzed using ELISA assays. Results In the non-specialized clinic, mean values rose from 2.66 ± 0.68 prior to therapy to 4.06 ± 0.70 during diagnosis, ultimately reaching 5.37 ± 1.14 post-treatment (F = 243.383, p < 0.001). At the specialized clinic, levels increased from 2.27 ± 0.75 to 2.00 ± 0.74, and subsequently to 3.34 ± 1.02 following therapy (F = 37.958, p < 0.001). Comparisons between groups revealed statistically significant variations in α-amylase levels at all time intervals (p < 0.05), with continuously elevated values noted in the non-specialist clinic.Conclusion: Children attending pediatric dental clinics are less prone to stress than those treated at regular dental clinics, salivary alpha-amylase is a reliable physiological biomarker of dental stress, Environmental and emotional stresses exert a greater influence on SAA secretion than self-perceived stress.